PEMBERDAYAN MASYARAKAT BERPROFESI PEDAGANG KAKI LIMA DI KOTA MALANG: bureaucracy, empowerment, society - Hartoko, Suryo; Yusnanda, Hilman (JAMAK, 2018)
In accordance with the title of this article, the author initially discussed the problem of street vendors or commonly called street vendors circulating in Malang City, where the focal point of this article is directed towards the people who feel the pros and cons of the existence of street vendors circulating widely in Malang which will have an impact on the economy of the street vendors themselves which has become their daily livelihood. This article also discusses trade land related to the use of space and roads that have been contained in the Government Law which at times interferes with comfort, security, and is focused also on community empowerment, the role of the government that intervenes in community empowerment, how the community can be empowered to reach their true point, and not depend on what they usually do. Also how is the role of the bureaucracy in this period related to the implementation of community empowerment that requires sustained efforts that require long sacrifices.